Enterovirus A71 utilizes host cell lipid β-oxidation to promote its replication - Yang, Xiuwen; Chen, Jiayi; Lu, Zixin; Huang, Shan; Zhang, Shihao; Cai, Jintai; Zhou, Yezhen; Cao, Guanhua; Yu, Jianhai; Qin, Zhiran; Zhao, Wei; Zhang, Bao; et al. (Frontiers in Microbiology, 2022)
Enterovirus A71 (EV-A71) is a major pathogen that causes severe and fatal cases of hand-foot-and-mouth disease (HFMD), which is an infectious disease that endangers children’s health. However, the pathogenic mechanisms underlying these severe clinical and pathological features remain incompletely understood. Metabolites and stress are known to play critical roles in multiple stages of the replication of viruses. Lipid metabolism and ER stress is an important characterization post viral infection. EV-A71 infection alters the perturbations of intracellular lipid homeostasis and induces ER stress. The characterization induced by viral infections is essential for optimal virus replication and may be potential antiviral targets. In this study, we show that additional the chemical drug of ER stress, PKR IN, an inhibitor, or Tunicamycin, an activator, reduced viral replication significantly, with the decrease of lipid. The replication of viruses was reduced by Chemical reagent TOFA, an inhibitor of acetyl-CoA carboxylase(ACC) or C75, an inhibitor of fatty acid synthase (FASN), while enhanced by oleic acid (OA), which is a kind of exogenous supplements of triacylglycerol. The pharmacochemical reagent of carnitine palmitoyltransferase 1 (CPT1) called Etomoxir and knocked down CPT1 induced EV-A71 replication to decrease. This suggests that lipid, rather than ER stress, is the main factor affecting EV-A71 replication. In conclusion, this study revealed that it is the β-oxidation of lipid that plays a core role, not ER stress, which is only a concomitant change with no restrictive effect, on virus replication.